Longitudinal physiological monitoring and evidence-based training periodization in junior cross-country skiers - Ver, A. (American Impact Review, 2026)
Purpose: This longitudinal case study examined the efficacy of systematic physiological monitoring in guiding individualized training periodization for junior cross-country skiers across three consecutive competitive seasons.